The reasons why parents choose to transfer students with special educational needs from Irish immersion education. (2nd January 2022) - Nic Aindriú, Sinéad
Abstract: There have been many instances when parents have been advised by educational professionals against bilingualism or immersion education for their child with special educational needs (SEN). Some parents follow the advice given and decide to use only one language with their child, mainly the majority language of the community. This study investigated the reasons why students with SEN transferred from Irish immersion primary education in the Republic of Ireland. The data presented contains information from a questionnaire completed by a random stratified sample of Irish immersion primary schools (20%, N = 29). It also contains data from semi-structured interviews with the parents of six students with a range of SEN who transferred from this form of education due to their learning difficulties. Questionnaires were analysed using SPSS and the interviews were analysed using thematic analysis. The findings of this study are particularly important, as internationally, the reasons why students with SEN transfer from immersion education is under researched. Furthermore, having an understanding of why these transfers occur will enable Irish immersion education and other forms of immersion education to gain an insight as to how they can adjust their practices in order to better meet the needs of all their students and subsequently, improve their student achievement and retention rates.